Controlling the s -wave scattering length with nonresonant light: Predictions of an asymptotic model - Crubellier, Anne; Gonzalez-Ferez, Rosario; Koch, Christiane P.; Luc-Koenig, Eliane (Physical Review A, 2017)
A pair of atoms interacts with nonresonant light via its anisotropic polarizability. This effect can be used to tune the scattering properties of the atoms. Although the light-atom interaction varies with interatomic separation as 1/R3, the effective s-wave potential decreases more rapidly as 1/R4 such that the field-dressed scattering length can be determined without any formal difficulty. The scattering dynamics are essentially governed by the long-range part of the interatomic interaction and can thus be accurately described by an asymptotic model [A. Crubellier, New J. Phys. 17, 045020 (2015)NJOPFM1367-263010.1088/1367-2630/17/4/045020]. Here we use the asymptotic model to determine the field-dressed scattering length from the s-wave radial component of a particular threshold wave function. Applying our theory to the scattering of two strontium isotopes, we calculate the variation of the scattering length with the intensity of the nonresonant light. Moreover, we predict the intensities at which the scattering length becomes infinite for any pair of atoms.
CRIS-Team Scopus Importer:2023-04-20